Science education and labor market outcomes in a developing economy. - Jain, Tarun; Mukhopadhyay, Abhiroop; Prakash, Nishith; Rakesh, Raghav (Economic Inquiry, 2022)
We examine the association between studying science in higher secondary school and labor market earnings in India. Studying science in high school is associated with 22% greater earnings than studying business or humanities. Earnings for science students are further enhanced with some fluency in English. Science education is also associated with more years of education, completing a professional degree, returns to entrepreneurship and working in public sector positions. Primary survey of high school students shows no discernible differences in behavioral characteristics of science students compared to others.